Teori dan Penemuan Hukum (Rechtsvinding) oleh Hakim Pada Tingkat Kasasi Terkait Putusan Pengadilan Negeri Nomor: 796/Pid.B/2022/Pn.Jkt.Sel Vonis Mati yang Diubah Menjadi Penjara Seumur Hidup dalam Putusan Mahkamah Agung Nomor: 813.K/Pid/2023) - Muhammad Rendy Adhitya; Muhammad Sidiq Alfatoni; Tasya Gita Irwanda; Siti Rifqa Raihani; Irwan Triadi (Media Hukum Indonesia (MHI), 2026)
Pretrial proceedings (praperadilan) constitute an important innovation within the Indonesian Criminal Procedure Code (KUHAP) as an instrument for protecting the rights of suspects against arbitrary actions by law enforcement officials. However, since the Decision of the South Jakarta District Court Number 796/Pid.B/2022/PN.Jkt.Sel, the authority of pretrial proceedings has undergone significant development through the expansion of its objects to include the determination of suspects. This decision marks the occurrence of legal discovery (rechtsvinding) by the judge, who interpreted Article 77 of the KUHAP progressively based on the principles of human rights protection and the due process of law. This study aims to analyze the decision from the perspective of theories of justice, particularly Aristotle’s concept of justice. The method used is normative juridical analysis of judicial decisions and their legal reasoning. The results of the study indicate that the decision reflects retributive justice moving toward a more rehabilitative and humanistic approach. However, within the framework of distributive and corrective justice, debates arise concerning the proportionality of the punishment, the defendant’s position as a former high-ranking police official, and public expectations of justice. The decision is legally valid, yet it still leaves moral and ethical questions in its implementation.